Rendahnya Keterlibatan Orang Muda Katolik dalam Kehidupan Menggereja sebagai Tantangan Katekese dalam Konteks Era Digital - Anjeli Sarma; Monica Innanda Chiaralazzo; Intansakti Pius X (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Catechesis is a process of faith formation that aims to help the faithful, especially Catholic youth, to know, internalize, and live out the Christian faith in their daily lives. In the digital era, youth participation in ecclesial life tends to decline, as indicated by low involvement in Church activities. This condition is influenced by various factors, such as academic and work commitments, as well as the dominance of digital culture, which is often more appealing to young people than spiritual activities. This study aims to analyze the role of catechesis in increasing the participation of Catholic youth in the digital era and to examine the relevance of retreats and recollections as contextual forms of catechesis. The research employs a qualitative approach using a literature study method, supported by observations of ecclesial life at the station level. The findings indicate that catechesis that is primarily informative is less effective in addressing the needs of young people, who seek a more personal and participatory faith experience. In this regard, retreats and recollections have the potential to serve as forms of catechesis that deepen faith experiences and encourage active participation in the life of the Church.